PENGARUH MODEL PROJECT BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK DI SMK AD-DIMYATI KOPO BANDUNG - Risa Khotimatun Nisa; Mohamad Gatah Adiansah; Abdul Holik (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
Learning in the industrial era 4.0 refers to developing the potential of students and growing and developing 4C skills. So far, students' creative thinking skills development has yet to be fully considered. The existence of a Project Based Learning learning model encourages students to think creatively. This research aims to deepen the study of the effect of the Project Based Learning learning model on increasing students' creative thinking skills. This study used a quantitative approach design with a quasi-experimental method. The research population is all class X students of SMK Ad-Dimyati Kopo Bandung in the 2022/2023 academic year, while the X-5 class sample is for the experimental class and the X-1 class is for the control class. The collected data were analyzed using the Man-Whitney U test. The Project-Based Learning Learning Model significantly affects students' creative thinking abilities with a significance value of 0.000 <0.05. Thus, this study concluded that the Project Based Learning learning model could be used as one of the learning innovations to develop 4C skills.